Factors associated with prenatal care and HIV and syphilis testing during pregnancy in primary health care - Cláudia Helena Soares de Morais Freitas; Franklin Delano Soares Forte; Angelo Giuseppe Roncalli; Maria Helena Rodrigues Galvão; Ardigleusa Alves Coelho; Sonia Maria Ferreira Dias
ABSTRACT OBJECTIVE To evaluate the factors associated with HIV and syphilis testing during pregnancy in Brazil. METHODS This was an ecological study covering all Brazilian municipalities evaluated by the second cycle of the National Program for Access and Quality Improvement in Primary Care, 2013-2014. The dependent variables were based on prenatal care access: prenatal care appointments, and HIV and syphilis tests during prenatal care. The independent variables were compared with demographic and social characteristics. Bivariate analysis was performed assessing the three outcomes with the independent variables. Variables with significant associations in this bivariate analysis were fit in a Poisson multiple regression analysis with robust variance to obtain adjusted estimates. RESULT Poisson regression analysis showed a statistically significant association with the variables "less than eight years of study" [prevalence ratio (PR) = 1.31; 95%CI 1.19-1.45; p < 0.001] and "participants of the cash transfer program" (PR = 0.80; 95%CI 0.72-0.88; p < 0.001) for the outcome of "having less than six prenatal care appointments" and individual variables. A statistically significant association was found for "participants of the cash transfer program" (PR = 1.43; 95%CI 1.19-1.72; p < 0.001) regarding the outcome from the comparison between HIV testing absence during prenatal care and demographic and social characteristics. The absence of syphilis testing during prenatal care, and demographic and social characteristics presented a statistically significant association for the education level variable "less than eight years of study" (PR =1.75; 95%CI 1.56-1.96; p < 0.001) and "participants of the cash transfer program" (PR = 1.21, 95%CI 1.07-1.36; p < 0.001). CONCLUSIONS The individual factors were associated with prenatal care appointments and HIV and syphilis tests in Brazilian pregnant women. They show missed opportunities for diagnosing HIV and syphilis infection during prenatal care and indicate weaknesses in the quality of maternal health care services to eliminate mother-to-child transmission.